Temperature-Sensitive Gels for Intratumoral Delivery of β-Lapachone: Effect of Cyclodextrins and Ethanol - Marcilio S. S. Cunha-Filho; Carmen Alvarez-Lorenzo; Ramón Martínez-Pacheco; Mariana Landin (The Scientific World Journal)
This work evaluated the potential of Pluronics (varieties F127 and P123) in combination with solubilizing agents to be used as syringeable in situ gelling depots of intratumoral β-lapachone (βLAP). Pluronic dispersions prepared at various concentrations in the absence and the presence of ethanol and randomly methylated β-cyclodextrin (RMβCD) were characterized regarding their rheological properties, drug solubilization capacity, and in vitro release. Pluronic F127 (18–23%) formulations combined high ability to solubilize βLAP (enhancement solubility factor up to 50), adequate gel temperature range (over 25°C), and gel strength at 37°C enough to guarantee the permanence of the formulation in the administration site for a period of time. βLAP release rate was finely tuned by the concentration of the polymer and the addition of RMβCD (diffusion coefficient ranging between 9 and 69 μg·cm−2). The ethanol increases βLAP release rate but simultaneously led to weak gels. This paper shows that βLAP formulations involving temperature-reversible Pluronic gels may be suitable for intratumoral drug delivery purposes.